Phylogenetic analysis of the circum-Antarctic Subfamily Migadopinae (Coleoptera, Carabidae) and assessment of the trans-Tasman Amarotypus clade - Liebherr, James K. (2024)
Phylogenetic analysis of Migadopinae Chaudoir, 1861, based on morphological characters analyzed using maximum parsimony and Bayesian inference, recognizes the tribal adelphotaxa Aquilicini Moret, 2005 and Migadopini. Amarotypini Erwin, 1985 (type genus Amarotypus Bates, 1872) is newly synonymized with Migadopini, as its taxonomic recognition renders Migadopini paraphyletic. Phylogenetic relationships within Migadopinae establish the Andean tropicomontane Aquilex Moret, 1989—type genus of the monogeneric Aquilicini—as sister group to the circum-Antarctic Migadopini. The earliest-diverging member taxa of Migadopini are distributed across southern South America and the subantarctic Falkland Islands. Subsequent divergence implicates Australia, New Zealand, and the Campbell Plateau. Internodes of the taxon-area cladogram are optimized using RASP (Reconstruct Ancestral State in Phylogenies), with nodal optimizations interpretable by both vicariance or dispersal. Campbell Plateau taxa are ambiguously derived from an ancestral node optimized to either South America, Australia, or the Campbell Plateau itself, a result most consistent with fragmentation of these Gondwanan terranes. Only the origin of the Tasmanian Migadopiella Baehr—taxonomically placed within a paraphyletic assemblage comprising the New Zealand genera Amarotypus, Amaroxenus Larochelle & Larivière, and Amarophilus Larochelle & Larivière—is interpreted unambiguously as dispersal based, in this instance via east to west trans-Tasman dispersal. Winged flight by migadopine carabid beetles, previously hypothesized as a vehicle for dispersal between Australia and South America, is dismissed based on restriction of macropterous taxa to two disparate and highly subordinate taxa; one comprising the Australian tropicomontane Dendromigadops Baehr and its temperate rainforest-occupying sister genus Decogmus Sloane, and the second, Antarctonomus complanatus of Valdivian and Magellanic Nothofagus forest in Chile and Argentina. Relevant fossil evidence supporting austral relationships of Migadopinae is briefly reviewed, including the mid-Cretaceous occurrence of Migadopinae in Kachin Burmese Amber, and the Miocene-aged fossil carabid beetle, Antarctotrechus balli Ashworth and Erwin (Trechini), described from the trans-Antarctic Mountains. The former supports a Cretaceous origin for Migadopinae consistent with Austral vicariance, the latter augurs the discovery of biogeographically homologous Antarctic fossil representatives that could corroborate an Austral vicariance hypothesis for the migadopine radiation.